2015
DOI: 10.3390/ijerph120809799
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Exposure to Second-Hand Smoke among Urban Residents: A Community-Based Investigation

Abstract: Objectives: In 2005, China acceded to the World Health Organization Framework Convention on Tobacco Control (WHO FCTC), the foundation for the global fight against tobacco. Certain cities in China have established local regulations to control tobacco use ahead of national policy; however, without the enforcement of statutory law, some of these regulations are merely lip service. The aim of the study was to assess the effects of city policy on smoking prevalence and on second-hand smoke (SHS) exposure status am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This shows that almost half of the non-smoking participants are also at risk of developing cardiovascular disease, as secondary smoking has been implicated in increasing cardiovascular risk by 25-30% and no safe limit has been established. 45 Likewise, Xu et al 46 also reported higher exposure to secondary smoke at home among women. The higher rate found among women is expected.…”
Section: Discussionmentioning
confidence: 96%
“…This shows that almost half of the non-smoking participants are also at risk of developing cardiovascular disease, as secondary smoking has been implicated in increasing cardiovascular risk by 25-30% and no safe limit has been established. 45 Likewise, Xu et al 46 also reported higher exposure to secondary smoke at home among women. The higher rate found among women is expected.…”
Section: Discussionmentioning
confidence: 96%
“… 10 Many large cities have local regulations regarding tobacco control, but the effect has been less than expected. 11 12 China is the largest tobacco grower and consumer in the world. Chinese national legislators have actively started the process of national bans on smoking in public and work places since 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising especially given attempts by some cities and provinces to restrict smoking [ 33 ]. However, smoking in smokefree public places has neither come under strong public condemnation nor faced strong penalties, so smoking and exposure to SHS continues to be a common phenomenon in these venues [ 34 – 36 ]. So the question arises, therefore, of the extent to which the presence of SFRs has any effect on patterns of exposure.…”
Section: Introductionmentioning
confidence: 99%